Design and implementation of a container-based virtual client architecture for interactive digital signage systems - Youngki Park; Hyunsik Yang; Thanh Dinh; Younghan Kim (International Journal of Distributed Sensor Networks)
Interactive digital signage is an important Internet of things application and has been becoming a common type of human–machine interface for multiple users. By integrating with wireless sensor networks, a digital signage system can provide smart features and on-demand contents to users. However, the performance of current interactive digital signage systems depends heavily on the server. An increasingly high number of digital signage clients and sensor devices attached to the system generating a huge amount of traffic flowed to the server may create bottleneck, management and scalability issues at the server, especially in large-scale digital signage systems. In addition, the current system requires application installation and configuration at the client side, thus leading to a high cost and complexity of deployment as well as management. This article proposes and implements a container-based distributed virtual client architecture for interactive digital signage to solve the above issues. In the proposed architecture, a number of digital signage clients and Internet of things devices are virtualized and managed by a container-based middleware. Each container-based middleware is responsible to manage and process data for a cluster of digital signage clients and corresponding Internet of things devices to (1) reduce load to server and improve the service performance and (2) enable lightweight clients to reduce cost and complexity in deployment as well as management. Implementation and obtained analysis results show the advantages of the proposed architecture.